Modeling and optimization of physical properties and sensory characteristics of squash (Cucurbita maxima duchesne) - corn (Z. saccharate stuart) chips formulation using response surface methodology - Labartine, Elvira Cabadsan; Galvez, Flor Crisanta F. (1999)
The formulation for a squash-corn chip product was optimized using response surface methodology (rsm). A mixture design was used to determine the amounts of squash puree(40-60%), corn flour (35-60%), and modified starch descriptive sensory properties of commercial samples. Results indicated that a squash corn chip product that is comparable with commercial samples maybe produced using 8-14% modified starch and 48-60% squash puree. This product will have color lightness value. L=49.9-52.1; fracturability =159.4-303.3g; hardness= 1616-1818g; and the following descriptive sensory scores: color=105-130 (#1 Roche yolk color fan=12.5; #10 Roche yolk color fan =137.5, sweetness= 135 - 195 (2% sugar solution= 20; 16% sugar solution= 150), saltiness 65-70 (0.02% salt=25; 0.7% solution = 150), spiciness=38-52 (2% sugar solution =20; 5% sugar solution=50), and hardness= 87-95 (cream cheese=10; hard candy=150) using 150-mm unstructured line scales.
Thesis (M. S. Food Science)--University of the Philippines, Diliman.
Keywords: Snack foods; Corn products